A study of thermal behavior for automotive dry clutch disc component - Muhd Ridzuan, Mansor; Mohd Zaid, Akop; Ahmad Rivai; Mohd Afzanizam, Mohd Rosli; Nurfaizey, Abdul Hamid (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.